The influence of the behavior of hypertensive patients on efforts to minimize stroke attacks in community health centers Ri Sidomulyo Riau - Sihombing, Reny Juliana (Sean Institute, 2022)
Hypertension is a disease that arises due to the interaction of various risk factors that a person has. This disease can be experienced by anyone, especially older people. The method in this research is a type of correlation research which aims to analyze the influence of the behavior of hypertensive patients on efforts to minimize stroke attacks at the Ri Sidomulyo Riau Community Health Center in 2023. The population of this study was 1532 people. The sample in this study amounted to 39 people based on purposive sampling technique. The data used is primary by distributing questionnaires to respondents. The results obtained from the knowledge of hypertensive patients regarding dietary management were quite good for the majority, as many as 21 people (53.8%), The majority of hypertensive patients' knowledge about exercise is quite good, 17 people (43.6%), the majority of hypertensive patients' knowledge about weight loss is quite good, 20 people (51.3%) and the majority of hypertensive patients' knowledge about avoiding stress is not good, 17 people. (43.6%). So it can be concluded from this research that there is an influence on the behavior of hypertensive patients on efforts to minimize stroke attacks based on diet regulation, regular exercise and weight loss in the majority which is quite good, while the majority of stress management is not good. Health workers at the Ri Sidomulyo Riau Community Health Center are expected to be able to provide more complete and comprehensive health information.